1989
DOI: 10.1159/000181109
|View full text |Cite
|
Sign up to set email alerts
|

Normoreninemic Hypoaldosteronism in a Case of Isolated ACTH Deficiency

Abstract: This paper documents the rare and hitherto unreported association between isolated ACTH deficiency and normoreninemic hypoaldosteronism in a 63-year-old woman. Baseline plasma aldosterone and 18-hydroxycorticosterone were extremely low. Both steroids did not respond to exogenous angiotensin II infusion, whereas they were increased in parallel to ACTH stimulation. Thus, acquired dysfunction or congenital dysgenesis of the zona glomeruk > sa was suspected. The upright posture-furosemide test showed a subnormal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Since acute GC withdrawal has an influence on the Nephron 1996;73:301-304levels of PRA and Aid in hypopituitarism [12], it is possi ble that some effect of GC on the levels of PRA and Aid existed in their study. Miyabo et al [14] also reported a case of isolated ACTH deficiency with normoreninemic hypoaldosteronism. Although a relation between renin release stimulation test and the replacement therapy was unclear in the case, hypoaldosteronism persisted after GC therapy.…”
Section: Fig 2 the Comparison Of Urine Volume (Uv)mentioning
confidence: 96%
“…Since acute GC withdrawal has an influence on the Nephron 1996;73:301-304levels of PRA and Aid in hypopituitarism [12], it is possi ble that some effect of GC on the levels of PRA and Aid existed in their study. Miyabo et al [14] also reported a case of isolated ACTH deficiency with normoreninemic hypoaldosteronism. Although a relation between renin release stimulation test and the replacement therapy was unclear in the case, hypoaldosteronism persisted after GC therapy.…”
Section: Fig 2 the Comparison Of Urine Volume (Uv)mentioning
confidence: 96%